Perilaku Hidup Bersih dan Sehat (PHBS) Siswa di SDN Gerendong 1 dan SDN Gerendong 2, Kecamatan Keroncong, Kabupaten Pandeglang - Dian Hestiyantari; Yudi Chadirin; Heriansyah Putra; Bella Yuliani; Fauzan Subeantoro; Moch Ridwan Widiansyah; I Wayan Wirya Aristyana; Mochammad Izzudin Ma’mun; Abdul Malik; Angie Irmajulianna; Layla Alifani Ekrep (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Health is an important factor in efforts to develop Human Resources (HR), including education. This is due to the large amount of disease data that occur in school-age children (ages 610) such as intestinal worms (60-80%) based on data from the Indonesian Ministry of Health and dental caries (74%). Based on the results of observations that have been made at SDN Gerendong 1 and SDN Gerendong 2, most students are still littering due to the unavailability of rubbish bins, in addition to the unavailability of school canteens and a place to wash hands, making the PHBS activities in the school has not been carried out properly. PHBS is a strategy used to create independence in creating and achieving health and is a behavior that is applied based on awareness. This study aims to provide knowledge about PHBS in Gerendong 1 SDN and Gerendong 2 SDN Koroncong District. The study population was students in grades 3 and 4 elementary schools with a total of 120 students. Data analysis used the results of the pretest and posttest and the percentage statistical method. The results showed that as many as 111 students or 93% were able to sort waste properly and as many as 113 students or 94% were able to wash their hands properly and correctly from the total number of students. Based on these data all students both SDN 1 Gerendong and SDN 2 Grerendong can already understand the material that has been given and can practice it correctly. Keywords: PHBS, SDN Gerendong 1, SDN Gerendong 2, student